Osteoarthritis of the knee - Bonnin, Michel. (Springer, 2008)
This work aims to summarize clearly the current concepts in the surgical treatment of osteoarthritis of the knee, including high tibial or femoral osteotomy, unicompartmental knee arthroplasty and total knee arthroplasty. This book can be read at different levels: basic chapters are particularly dedicated to non-specialized or junior surgeons, rheumatologists, radio logists and physiotherapists. More specialized aspects dealing with difficult cases and controversial topics are dedicated to highly specialized surgeons. Numerous chapters focus on difficult cases in primary TKA, such as TKA on stiff knees, TKA in case of severe deformity or TKA following HTO or failed UKA. Strategy and options in revision TKA are also discussed in the second part of the book. Thanks to its didactic approach, the reader will find quick answers to technical or conceptual difficulties. The use of numerous figures, X-rays and algorithms clarifies the statements and guides the reader throughout this book. Generality -- Imaging knee osteoarthritis -- Patellofemoral osteoarthritis -- ACL and arthritis -- The medical treatment of gonarthrosis -- Surgical Treatment -- Technique in high tibial osteotomy -- Opening wedge osteotomy of the distal femur in the valgus knee -- Unicompartmental knee arthroplasty — Results, causes of failure, indications -- Unicompartmental knee arthroplasty — Technical principles -- Surgical indications in tibiofemoral arthrosis (TFA) -- Points of view: What are the limits in ACL reconstruction? -- Total Knee Arthroplasty -- History, evolution of concepts, various current prostheses -- Results of total knee arthroplasty -- Failure mechanisms in total knee arthroplasty -- Rehabilitation after total knee arthroplasty -- French anesthesia for total knee arthroplasty: Medical management during the perioperative period -- Total knee replacement in severe genu varum deformity -- Total knee replacement in the valgus knee -- Total knee arthroplasty for the stiff knee -- Total knee arthroplasty after tibial valgus osteotomy -- Total knee arthroplasty after failed unicompartmental knee arthroplasty -- Soft tissue balancing in total knee arthroplasty -- Extensor mechanism related complications in total knee arthroplasty Diagnosis — Treatment — Prevention -- Femoral rotation in totak knee arthroplasty -- Bone loss with total knee replacement -- Revision total knee arthroplasty for aseptic failure -- Management of bone defects in revision total knee arthroplasty -- Choice of constraint in revision total knee arthroplasty -- Two-stage reimplantation for infected total knee arthroplasty — Results at 5-year follow-up -- Osteoarthritis of the knee — Soft tissue defect problems: Prevention and treatment -- Computer-assisted navigation in total knee replacement -- Conservation of posterior cruciate ligament in fixed-bearing total knee replacement... Substitution of the posterior cruciate ligament in total knee arthroplasty: Advantages and pitfalls -- Fixation with or without cement in total knee arthroplasty -- The mobile plateau in total knee arthroplasty -- Rotation in total knee arthroplasty -- Steps and strategies in the insertion of posterior-stabilized knee replacements.